The Fungi-specific histone Acetyltransferase Rtt109 mediates morphogenesis, Aflatoxin synthesis and pathogenicity in Aspergillus flavus by acetylating H3K9 - Ruilin Sun; Meifang Wen; Lianghuan Wu; Huahui Lan; Jun Yuan; Shihua Wang (IMA Fungus)
Abstract Aspergillus flavus is a common saprophytic filamentous fungus that produces the highly toxic natural compound aflatoxin during its growth process. Synthesis of the aflatoxins, which can contaminate food crops causing huge losses to the agricultural economy, is often regulated by epigenetic modification, such as the histone acetyltransferase. In this study, we used Aspergillus flavus as an experimental model to construct the acetyltransferase gene rtt109 knockout strain (△rtt109) and its complementary strain (△rtt109·com) by homologous recombination. The growth of △rtt109 was significantly suppressed compared to the wild type (WT) strain and the △rtt109·com strain. The sclerotium of △rtt109 grew smaller, and the amount of sclerotia generated by △rtt109 was significantly reduced. The number of conidiums of △rtt109 was significantly reduced, especially on the yeast extract sucrose (YES) solid medium. The amount of aflatoxins synthesized by △rtt109 in the PDB liquid medium was significantly decreased We also found that the △rtt109 strain was extremely sensitive to DNA damage stress. Through the maize seed infection experiment, we found that the growth of △rtt109 on the surface of affected corn was largely reduced, and the amount of aerial mycelium decreased significantly, which was consistent with the results on the artificial medium. We further found that H3K9 was the acetylated target of Rtt109 in A. flavus. In conclusion, Rtt109 participated in the growth, conidium formation, sclerotia generation, aflatoxin synthesis, environmental stress response, regulation of infection of A. flavus. The results from this study of rtt109 showed data for acetylation in the regulation of life processes and provided a new thought regarding the prevention and control of A. flavus hazards.